1986
DOI: 10.1007/bf00028559
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of resistance to ascochyta blight in chickpea (Cicer arietinum L.)

Abstract: Six chickpea lines resistant to Ascochyta rabiei (PASS.) LAB. were crossed to four susceptible cultivars. The hybrids were resistant in all the crosses except the crosses where resistant line BRG 8 was involved. Segregation pattern for diseases reaction in F2, BCPI, BCP2 and F3 generations in field and glasshouse conditions revealed that resistance to Ascochyta blight is under the control of a single dominant gene in EC 26446, PG 82-1, P 919, P 1252-1 and NEC 2451 while a recessive gene is responsible in BRG 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 3 publications
0
33
2
Order By: Relevance
“…To date, the pathogen has been classified mainly into two broad pathotypes: pathotype I (less aggressive) and pathotype II (aggressive) ; but further research is required to identify the genes that control aggressiveness. As for the host, early studies on the inheritance of blight resistance indicated that it could be conferred by one, two or three genes (Singh and Reddy 1983;Tewari and Pandey 1986;Dey and Singh 1993;Tekeoglu et al 2000). Furthermore, evidence that resistance might be inherited as a quantitative trait has been reported (Muehlbauer and Kaiser, 1994).…”
Section: 贸 Knpv 2007mentioning
confidence: 97%
“…To date, the pathogen has been classified mainly into two broad pathotypes: pathotype I (less aggressive) and pathotype II (aggressive) ; but further research is required to identify the genes that control aggressiveness. As for the host, early studies on the inheritance of blight resistance indicated that it could be conferred by one, two or three genes (Singh and Reddy 1983;Tewari and Pandey 1986;Dey and Singh 1993;Tekeoglu et al 2000). Furthermore, evidence that resistance might be inherited as a quantitative trait has been reported (Muehlbauer and Kaiser, 1994).…”
Section: 贸 Knpv 2007mentioning
confidence: 97%
“…These studies showed that in some desi chickpeas, and in several kabuli chickpeas (ILC 72,ILC 183,ILC 200 and ILC 935), a single dominant gene controlled resistance (Vir et al 1975;Singh and Reddy 1983). In some other cultivars, it has been reported that resistance was governed by two dominant genes (Tewari and Pandey 1986), one recessive gene (Tewari and Pandey 1986), two recessive genes (Kusmenoglu 1990) or by two to three quantitative loci , depending on the screening techniques and the cultivar used.…”
Section: Introductionmentioning
confidence: 95%
“…However, using an F 2 population from the same parental lines that were used by Ahmad et al (1952), Hafiz and Ashraf (1953) showed that blight resistance was conferred by one dominant gene. A dominant genetic mechanism for blight resistance had been supported by many reports (Vir et al 1975;Singh and Reddy 1983;Tewari and Pandey 1986) until Kusmenoglu et al (1990), using a population of F 2 -derived F 3 families, reported that blight resistance was conferred by two recessive genes acting additively. confirmed the recessive genetic nature of blight resistance, using three recombinant inbred line (RIL) populations that were derived from crosses of resistant and susceptible germplasm lines.…”
Section: Introductionmentioning
confidence: 97%